2019
DOI: 10.1186/s12917-018-1762-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of a Fasciola gigantica serum antibody ELISA to estimate prevalence in cattle in Cameroon

Abstract: BackgroundCattle rearing in Cameroon is both economically and culturally important, however parasitic diseases detrimentally impact cattle productivity. In sub-Saharan Africa bovine fasciolosis is generally attributed to F. gigantica, although understanding of Fasciola species present and local epidemiology in individual countries is patchy. Partly limited by the lack of representative surveys and understanding of diagnostic test perfromance in local cattle populations. The aims of this paper were to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…However, Bafia at 467 m asl is not so high; therefore, it is unclear why no infections were found. A study that was carried out in 2012/2013 suggested a prevalence of 0.4% in cattle at the Bamenda abattoir, around 80 km from Bafoussam, which may suggest that there is a low prevalence within this area (Kelly et al ., 2019). Further work should be undertaken to investigate fascioliasis in these areas and to examine if the snail intermediate host is present.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bafia at 467 m asl is not so high; therefore, it is unclear why no infections were found. A study that was carried out in 2012/2013 suggested a prevalence of 0.4% in cattle at the Bamenda abattoir, around 80 km from Bafoussam, which may suggest that there is a low prevalence within this area (Kelly et al ., 2019). Further work should be undertaken to investigate fascioliasis in these areas and to examine if the snail intermediate host is present.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa (SSA), fascioliasis has been reported in West Africa [12,31], East Africa [32], and South African countries [33,34]. However, it has also been reported in Egypt (outside SSA), North Africa [35,36].…”
Section: The Distribution Of Fascioliasismentioning
confidence: 99%
“…Fascioliasis due to F. g igantica is predominantly endemic in the lower altitudes of tropical and subtropical parts of the world. Consequently, more cases of the disease are reported in larger part of sub-Saharan Africa (SSA) where suitable snail intermediate hosts naturally inhabit [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, more disease cases are being recorded in a more significant portion of Sub-Saharan Africa (SSA), where suitable snail intermediate hosts occur naturally (Kelly et al 2019). Due to the high prevalence of Fasciolid infection in humans, this disease has been underestimated.…”
Section: A Neglected Diseasementioning
confidence: 99%